A study of pre-briquetting granulation sintering of the mixtures with high ratio of Brazilian specularite concentrate. (25th November 2016) - Zhu, D.; Guo, Z.; Pan, J.; Zhang, F.
Abstract : In the paper, the pre-treatment of fine Brazilian specularite concentrates with high iron grade and low impurities through pre-briquetting was proposed to improve the granulation and sintering performance of blends comprising some 30% specularite concentrates. The results show that the excellent sintering indexes are attained as follows in pot tests: productivity of 1.64 t m −2  h −1, tumble index of 59.87% and solid fuel consumption of 71.64 kg t −1 under the optimal conditions. Compared with traditional sintering process, productivity and tumble index were increased by 13.88 and 3.5%, respectively, and solid fuel consumption decreased by 4.82 kg t −1 . The RI and RDI−3.15 reach 83.95 and 35.02%, respectively, which are superior for blast furnace. The mechanism of the pre-treatment of the specularite concentrates was demonstrated that better permeability was achieved by coarsening granule, more calcium ferrite was formed by basicity segregation and separation addition of coke.